Evaluation of Stories of the Prophets in the Holy Qur'an Based on Existential Therapy - Harun Torun; Mustafa Tekke (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
This study aimed to examine the stories of 25 prophets mentioned in the Qur'an within the framework of the existential theory. The research has been studied on associating the prophets and their stories in the Qur'an with the concepts of the existential theory. While the life of the prophets was encountered with the existentially positive concepts of the existential theory, no relationship could be established with the negative concepts. Knowing that the prophets mentioned in the holy book of Islam, the Qur'an, can be associated with the concepts of existential theory is important because it can be beneficial in existential therapy studies with Muslims. In addition, the study finding is significant in terms of establishing a bridge between the Qur'an, which is the main element of Islam, and the existence of western philosophers and mental health experts.